Transforming the Process of Recognition of Medical Specialist in the Ministry of Health: A Shift from Specialist Gazettement to Supervised Work Experience - Ismail, Hirman; Yacob, Mohd Azman; Abdullah, Mohamed Hirman; Zun, Ahmad Badruridzwanullah; Osman, Sabrizan; Amran, Siti Baizura; Idris, Nur Ainina; Fakhrul Ruzi, Farah Ruwaida; Jalaluddin, Siti Norsyazwanis; Othman, Ahmad Yamany; Abdul Halim, Nora Eliza; Kamarulzaman, Nor Akmal Hakim (Malaysian Journal of Medical Sciences, 2025)
The supervised practice of newly credentialed medical practitioners within the public sector following completion of specialist training, referred to previously in Malaysia as specialist gazettement or post-qualification working experience (PQWE), is a unique regulatory mechanism aimed at safeguarding the quality and safety of specialist care. This probationary phase enables senior consultants or specialists to assess the competence and readiness of the practitioners for independent clinical practice. In response to evolving demands on healthcare delivery and workforce governance, the Ministry of Health has introduced a series of strategic reforms to strengthen its framework, especially within the public healthcare setting. These include legislative amendments to formalise and regularise the implementation of the probationary phase through supervised work experience or SWE (legal transformation), fiscal measures to support financing incentives (financial transformation), and digital innovations that enhance experience and administrative efficiency (digital transformation). This paper describes these transformative interventions, positioning the Ministry of Health’s approach within broader policy discourses on clinical governance and health system sustainability.